Análisis de la calidad de absorción y fragilidad visual de las unidades del paisaje del páramo Langoa del proyecto Novillopungo, propuesta de conservación 2023. - Llano Asas, Diana Carolina (2023)
The current research project was developed with the purpose by establishing the landscape unit’s absorption and visual fragility quality from Langoa moorland, located in the Juan Montalvo Parish, from Novillopungo project, with the GIS software help, it was elaborated several thematic maps, which helped to characterize studies some qualities from study area and through the methodologies application focused on the landscape units identification, what are: the Bureau of Land Management program with its Visual Resource Management method was achieved to determine the Visual Absorption Capacity, fragility and visual sensitivity, what allowed establishing qualitative values approaches with the photographs use taken from the study area, which allowed to give different values in several numerical weighting scales focused on determining components, such as color, shape, texture, line, dimension, and spatial scale and configuration. As results, it was established that the Langoa moorland has an average visual quality with a numerical value 17, its visual absorption capacity within the area was located in class I, with a value 16, determining, what the place landscape is very fragile, then, it is established conservation strategies based on a 4 social, cultural, environmental, economic and political nature components, in order to reduce the negative impacts generated by catchments with a focus on minimizing ecosystem alterations and degradation can conclude, which the study area requires establishing management activities, what ensure the natural landscape protection and conservation, in order to maintain its ecological integrity in the long term.